Fractal Characteristics and Acoustic Emission during the Failure Process of Argillaceous Siltstone with Different Moisture Contents - Haoran Song; Shouyu Li; Jiachen Xu; Qingwen Zhang; Yonghui Zhi (Geofluids)
Compressive strength and tensile strength are the critical parameters to determine rock performance, which can reflect the rock’s resistance to deformation and damage. Brazilian indirect tensile and uniaxial compression tests were carried out on rocks under different water immersion conditions to study acoustic emission (AE) characteristics and crack propagation during rock fracture. The test results show that water has a deteriorating effect on the argillaceous siltstone, with significant attenuation of both compressive and tensile strengths. With the increase in moisture content, the number of AE events decreased, the cumulative AE ringing count showed a gradual rise in steps, and the proportion of AE peak frequencies in the range of 0-200 kHz gradually increased. Natural rock samples are more brittle than water-saturated rock samples. The higher frequency of AE events and the higher energy released during the destruction of natural rock samples reflect in the clustering of high-energy AE source locus near the main rupture surface. The AE source locus is 1-2 energy levels higher in the vicinity of the fracture surface than in the water-saturated rock samples. The rock samples exhibited random packing of mineral particles and contained many clay minerals by SEM analysis of fracture microstructure. Water dissolves mineral particles and cementitious materials, producing microcracks with propagation potential. Analysis of the AE time sequence based on fractal theory reveals that fractal dimension value varies with the increase of moisture content. The variation of the fractal dimension D values for the water-saturated rock samples ranges from 0.4 to 0.65. This indicates that the number of microcracks is higher and their propagation more complex when the moisture content of the specimen is higher. The failure characteristics of the rock samples in the above research can provide a reference for monitoring rock mass stability under tunnel water inflow.